Follicular lymphoma: an Institutional Analysis - Gogia, Ajay (Asian Pac J Cancer Prev, 2017)
BACKGROUND: Follicular lymphoma (FL) is second most common lymphoma in adult, constituted 20% of all lymphoma cases in the west. There is limited information is available on FL from India. METHODS: The clinico-pathological profile, treatment outcome and prognostic factors for survival were assessed retrospectively in 181 patients of FL seen at our center over a period of 17 years (1996-2012). RESULTS: There were 120 males and 61 females. The median age was 51 years (24-80 years). The common presenting features were lymphadenopathy 71%, fatigue 23% and fever 20%. Ann Arbor stage distribution was: stage I - 9%, stage II - 11%, stage III -22 % and stage IV - 58%. Extra nodal involvement and bulky disease were present in 22% and 19% patients respectively. Follicular Lymphoma International Prognostic Index (FLIPI) 1 score : Low -25%, Intermediate-45% and high risk in 30% of cases. One forty five patients (80%) received treatment at presentation or during follow-up. Chemotherapeutic regimen used were: CHOP-45, CVP-51, chlorambucil and prednisolone -7, BR (bendamustine and rituximab)-12, RCHOP- 14 RCVP – 7 and other regimen were used in 5 cases. The overall response (ORR) and complete remission (CR) rates were 70% and 35% respectively. Median overall survival (OS) and event free survival (EFS) was 5.5 years and 2.5 years respectively, with median follow up period of 3.0 years. Grade 3 histology, failure to attain CR, low serum albumin, and high risk FLIPI were significantly associated with lower event free survival. High risk FLIPI (HR 1.46, 95% CI 1.03-2.10, p=0.003) and failure to attain CR (HR 2.64, CI 1.10-4.30, p=0.001) were predictors of poor OS. CONCLUSIONS: FL represents 9 % of all lymphoma in adult. This is the largest data from single institute from India. Eighty percentage of patients presented in stage III/IV disease. High risk FLIPI and failure to attain CR were important prognostic variables for OS.